The Absence of the Transient Receptor Potential Vanilloid 1 Directly Impacts on the Expression and Localization of the Endocannabinoid System in the Mouse Hippocampus - Egaña-Huguet, Jon; Bonilla-Del Río, Itziar; Gómez-Urquijo, Sonia M.; Mimenza, Amaia; Saumell-Esnaola, Miquel; Borrega-Roman, Leire; García del Caño, Gontzal; Sallés, Joan; Puente, Nagore; Gerrikagoitia, Inmaculada; Elezgarai, Izaskun; Grandes, Pedro (Frontiers in Neuroanatomy, 2021)
The transient receptor potential vanilloid 1 (TRPV1) is a non-selective ligand-gated cation channel involved in synaptic transmission, plasticity, and brain pathology. In the hippocampal dentate gyrus, TRPV1 localizes to dendritic spines and dendrites postsynaptic to excitatory synapses in the molecular layer (ML). At these same synapses, the cannabinoid CB1 receptor (CB1R) activated by exogenous and endogenous cannabinoids localizes to the presynaptic terminals. Hence, as both receptors are activated by endogenous anandamide, co-localize, and mediate long-term depression of the excitatory synaptic transmission at the medial perforant path (MPP) excitatory synapses though by different mechanisms, it is plausible that they might be exerting a reciprocal influence from their opposite synaptic sites. In this anatomical scenario, we tested whether the absence of TRPV1 affects the endocannabinoid system. The results obtained using biochemical techniques and immunoelectron microscopy in a mouse with the genetic deletion of TRPV1 show that the expression and localization of components of the endocannabinoid system, included CB1R, change upon the constitutive absence of TRPV1. Thus, the expression of fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) drastically increased in TRPV1−/− whole homogenates. Furthermore, CB1R and MAGL decreased and the cannabinoid receptor interacting protein 1a (CRIP1a) increased in TRPV1−/− synaptosomes. Also, CB1R positive excitatory terminals increased, the number of excitatory terminals decreased, and CB1R particles dropped significantly in inhibitory terminals in the dentate ML of TRPV1−/− mice. In the outer 2/3 ML of the TRPV1−/− mutants, the proportion of CB1R particles decreased in dendrites, and increased in excitatory terminals and astrocytes. In the inner 1/3 ML, the proportion of labeling increased in excitatory terminals, neuronal mitochondria, and dendrites. Altogether, these observations indicate the existence of compensatory changes in the endocannabinoid system upon TRPV1 removal, and endorse the importance of the potential functional adaptations derived from the lack of TRPV1 in the mouse brain.